How to design a sustainable heavy industrial estate - Galloway, D.; Newman, Peter (Elsevier, 2014)
The Mid West of Western Australia, south of the Pilbara, is developing as the next major mineral province in Australia. The province will be served by a new port at Oakajee and will be backed by a 4000 + ha greenfield industrial area. LandCorp, the State Government’s land development agency intends that the Oakajee Industrial Estate (OIE) will be a “sustainable industrial estate”. This paper describes the design process used to produce a flexible and adaptable layout of the estate to maximise use of renewable energy and minimise carbon emissions. The design and planning was complex because it had to anticipate a 50 year development program. Issues addressed included site characteristics and context, land allocation to optimise energy efficiency, embedding a multi-user co/tri-generation system in the middle of the estate, identify and estimating the production of energy from onsite and regional sources of renewable energy, options for reducing greenhouse emissions, waste reduction and reuse; and issues relating to the governance and management of the estate that will enable these site innovations to occur.